1971
DOI: 10.3181/00379727-136-35209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heparin on Endotoxin-Induced Thrombocytopenia

Abstract: In vitro studies with rabbit platelets have shown that relatively small concentrations of heparin are capable of preventing thrombin induced-platelet injury whereas very large amounts of the anticoagulant are necessary to prevent similar damage by bacterial endotoxin (1). In vivo investigations have demonstrated that the usual anticoagulating amounts of heparin do not prevent the thrombocytopenia in the generalized Shwartzman reaction (gSr) ( 2 ) in rabbits and a similar phenomenon has been observed in humans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1974
1974
1993
1993

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The use of heparin in patients with DIC is controversial. [40][41][42]44,81,158,188 Neither animal nor human studies have convincingly demonstrated a benefit from heparin. Furthermore, heparin is not without risk.…”
Section: Treatment Of Bacterial-induced Thrombocytopeniamentioning
confidence: 99%
“…The use of heparin in patients with DIC is controversial. [40][41][42]44,81,158,188 Neither animal nor human studies have convincingly demonstrated a benefit from heparin. Furthermore, heparin is not without risk.…”
Section: Treatment Of Bacterial-induced Thrombocytopeniamentioning
confidence: 99%
“…However, a low platelet count even in an appropriate clinical context does not, in the absence of other supportive findings, necessarily imply DIC. Thrombocytopenia is not uncommon in septicaemia, and in endotoxaemic rabbits low platelet counts occur despite pretreatment with heparin (Corrigan, 1971). …”
Section: Acute Dicmentioning
confidence: 99%